The Evening versus Morning Polypill Utilization Study: the TEMPUS rationale and design. (29th August 2020) - Lafeber, Melvin; Grobbee, Diederick E; Bots, Michiel L; Thom, Simon; Webster, Ruth; Rodgers, Anthony; Visseren, Frank LJ; Spiering, Wilko
Abstract: Background and rationale: In clinical practice, blood pressure (BP)-lowering agents are generally prescribed for use in the morning, whereas (short-acting) statins are recommended for use in the evening. There is evidence that the reduction in LDL cholesterol (LDL-c) achieved with short-acting statins is superior when taken in the evening and reported improvement in BP control when aspirin and BP-lowering agents are taken in the evening. However, it is unclear whether the additional reduction in LDL-c and BP is offset by a reduction in adherence, given that taking medication in the evening may be less typical or convenient. There is therefore uncertainty concerning the best timing of administration of a cardiovascular combination pill such as the polypill. Aim: The aim of TEMPUS (NCT01506505), a prospective randomized open blinded endpoint (PROBE) crossover trial, is to evaluate whether there is a difference in LDL-c levels or 24-hour ambulatory BP in individuals at increased risk of cardiovascular disease when the cardiovascular polypill is taken in the evening compared to the morning. An additional aim is to assess the effect of the polypill on LDL-c and BP compared to the administration of separate pills of identically dosed components of the polypill. Methods: In total 75 participants with established cardiovascular disease or an intermediate to high risk for cardiovascular disease are randomly allocated to the sequence of three different treatments of 6–8 weeks: (1) the cardiovascular polypill (aspirin 75 mg, simvastatin 40 mg, lisinopril 10 mg, and hydrochlorothiazide 12.5 mg) in the evening; (2) the polypill in the morning; and (3) the use of the identically dosed agents in separate pills taken at different time points during the day. The primary endpoint is the difference in LDL-c and mean 24-hour ambulatory systolic BP. Secondary outcomes are the difference in relative risk reduction, biochemistry, platelet function and pulse wave analysis, participants' adherence, and acceptability. Conclusions: TEMPUS will evaluate the effect of timing of the administration of a cardiovascular polypill on LDL-c and BP measurements in patients with an intermediate or high risk for cardiovascular disease.